The Correlation between Personality Type, Learning Motivation, and Ability to Read Poetry of Indonesian 10th Grade Students - Anggraeni, Nuni; Subandiyah, Henny; Mintowati, Mintowati (Universitas Galuh, 2024)
The conditions of human personality and motivation significantly influence all activities undertaken, including during the learning process. The ability to recite poetry is one of the learning achievements in the Indonesian language subject in the realm of literature. This research aims to identify the conditions of personality types, learning motivation, and the ability to recite literary poetry in vocational school (SMK) students. In addition to describing each component, these three variables will be interconnected to determine the strength of the relationships that occur. The research method used is a quantitative method with a correlational research design. The population used consists of 10th-grade students at SMKN 12 Surabaya, with the research sample being 32 students from the X-2 class majoring in Creative Metal Crafts and Jewelry. Data collection is carried out using questionnaire and observation techniques. After the data is collected, a multiple correlation analysis is performed with the aim of demonstrating the relationship between the three research variables. The results of this research include: 1) The personality type of X-2 students majoring in Creative Metal Crafts and Jewelry at SMKN 12 Surabaya tends to be introverted; 2) The learning motivation of X-2 students majoring in Creative Metal Crafts and Jewelry at SMKN 12 Surabaya is in the Very Low category; 3) The ability to recite poetry of X-2 students majoring in Creative Metal Crafts and Jewelry at SMKN 12 Surabaya is classified as insufficient or falls into category D; 4) The personality type (X1) and learning motivation (X2) variables together have a positive and significant correlation in the Moderate category with the ability to recite poetry variable (Y), with a correlation coefficient value of 0.526.